Empat Pilar Pendukung Daya Saing Pelaku Usaha Mikro Pada Sentra Wisata Kuliner Guminto di Surabaya - i putu - artaya (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2025)
This research study took place in Surabaya, precisely in Bulak Banteng Village. The object of the study is a culinary tourism center Guminto located in North Surabaya. The focus of the problem is to improve the competitiveness of the Guminto culinary tourism center. So that they are able to survive in competing with other culinary tourism centers. The total number of business actors engaged in the culinary field is 25 people with various types of food products, both food and beverages. The data collection model consists of interviews and filling out questionnaires. There are four variables used to improve competitiveness, i.e.: improving product quality, product change and innovation, increasing competitive advantage, and ensuring safe prices. The analysis method used is multiple linear regression analysis which aims to find the estimated equation. From the results of multiple linear regression analysis, it was found that the variables of improving product quality, product changes and innovations, and safe price variables turned out to be significant, meaning they were able to support or support the competitive strength of the Guminto culinary tourism center, but for the competitive advantage variable it turned out to be insignificant, meaning that to increase their competitiveness, the management in this case the Bulak Bantenng Village must focus on increasing the competitive advantage of the Guminto culinary tourism center with an approach to improving the capabilities of its human resources or business actors properly by providing training and assistance in the field of technology that is directly related to the culinary business in the Guminto culinary tourism center